2017
DOI: 10.4084/mjhid.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

FDG-Pet Scan: A New Paradigm for Follicular Lymphoma Management.

Abstract: In the present review, the reader will be led to the most relevant observations that prompted oncologists and haematologist to consider FDG-PET/CT as a new paradigm for FL management in clinical practice. The role of functional imaging in lymphoma staging, restaging, prognostication, and metabolic tumour volume computing will be reviewed in detail. Moreover, a special focus will be addressed to technical and practical aspects of PET scan reporting, which have been set during the last decade to ensure the repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
12
0
1
Order By: Relevance
“…It is hypothesized that, initially, follicular lymphoma is comprised of multiple clones that have an indolent behavior. Transformation occurs through the clonal evolution where the most aggressive clone undergoes expansion [5,16]. Most commonly, follicular lymphoma transforms into a DLBCL [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that, initially, follicular lymphoma is comprised of multiple clones that have an indolent behavior. Transformation occurs through the clonal evolution where the most aggressive clone undergoes expansion [5,16]. Most commonly, follicular lymphoma transforms into a DLBCL [17].…”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, CT and MRI are useful tools in assessing the extent of the disease. FDG-PET studies are instrumental in identifying patients with high risk of transformation [5].…”
Section: Introductionmentioning
confidence: 99%
“…A PET-CT scan was recommended recently for initial staging, identifying extranodal lesion and response assessment in both FL and DLBCL, which is more accurate and sensitive than contrast-enhanced CT scanning (12)(13)(14)(15). However, false-positive results with a PET-CT in FL have been described and occurred with inflammatory, normal physiologic processes, additional malignancy, and benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography (PET) is recognised as a standard post-treatment evaluation tool in FL, due to its ability to distinguish between viable residual tumour and necrosis or fibrosis in residual mass(es) often present after treatment, thereby allowing more precise response evaluation than CT [52]. Several studies have reported significantly longer PFS in patients with negative PET status at end of treatment compared with those with positive PET status [53][54][55].…”
Section: Complete Metabolic Response By Positron Emission Tomographymentioning
confidence: 99%